Factors affecting pregnant women’s compliance in consuming iron (Fe) tablets at Sukamakmur Public Health Center, Aceh Besar District - Nurlinda, Nurlinda; Gustiana, Gustiana; Manaf, Salmiani Abdul (Journal of Midwifery and Nursing, 2025)
Background: Anemia in pregnancy contributes to approximately 20% of maternal deaths globally. In Indonesia, anemia prevalence among pregnant women is 48.9%. National coverage of iron (Fe) supplementation (minimum 90 tablets) is 88.5%, yet in Aceh it is only 63.9%. At Sukamakmur Public Health Center, only 302 of 437 pregnant women (56.03%) receiving iron tablets were compliant, and 135 (25.05%) were diagnosed with anemia.Objective: To identify factors influencing compliance with iron tablet consumption among pregnant women in Sukamakmur, Aceh Besar District. Methods: This quantitative analytic descriptive study used a cross-sectional design involving 98 pregnant women in their second and third trimesters, selected through total sampling. Compliance was measured using the Morisky Medication Adherence Scale (MMAS-8). Knowledge, attitude, and family support were assessed using structured questionnaires. Data were analyzed with the chi-square test at p<0.05. Results: Most respondents had poor knowledge (48.0%), negative attitudes (53.1%), low family support (54.1%), and low compliance (72.4%). Significant associations were found between compliance and knowledge (p=0.000), attitude (p=0.033), and family support (p=0.011). Conclusion: Compliance remains low despite adequate distribution. Improving maternal knowledge, fostering positive attitudes, and enhancing family particularly husband support are essential to increase adherence and reduce anemia-related risks in pregnancy.